PENGARUH INDEPENDENSI, KOMPETENSI, PENGALAMAN, DAN AKUNTABILITAS AUDITOR TERHADAP KUALITAS JASA AUDIT (STUDI EMPIRIS PADA KAP DI JAKARTA) - Adang, Ferry (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
The purpose of this research is to examine empirically the influence of independency, competency,experience, and auditor’s accountability on audit quality. This research was conducted by distributing 159 piecesof questionnaires to the public accounting firm in Jakarta. Questionnaires were returned and in the content of 128pieces and are all used in this research. Double Linear Regression was used to the test of hypothesis. The resultof this research showed that independency had positive and significant influence on audit quality, competencyhad positive and significant influence in audit quality, experience had positive and significant influence in auditquality, and auditor’s accountability had positive and significant influence in audit quality.Key words: audit quality, auditor’s accountability, competency, experience, independency The purpose of this research is to examine the empirical influence of independency, competency, experience, and auditor’s accountability on audit service quality. This research was conducted by distributing 159 questionnaires to public accounting firms in Jakarta. 128 questionnaires were filled and returned and all of them were used in this research. Multiple Linear Regression method was used to test the hypothesis. The result of this research shows that independency has positive and significant influence on audit quality, competency has positive and significant influence on audit quality, experience had positive and significant influence on audit quality, and auditor’saccountability had positive and significant influence on audit quality.Keywords : Audit Service Quality, Auditor’s Accountability, Competency, Experience, Independency